1997
DOI: 10.1126/science.275.5302.945
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Selection for Catalysis in Combinatorial Antibody Libraries

Abstract: For the past decade the immune system has been exploited as a rich source of de novo catalysts. Catalytic antibodies have been shown to have chemoselectivity, enantioselectivity, large rate accelerations, and even an ability to reroute chemical reactions. In many instances catalysts have been made for reactions for which there are no known natural or man-made enzymes. Yet, the full power of this combinatorial system can only be exploited if there was a system that allows for the direct selection of a particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
102
0
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(114 citation statements)
references
References 36 publications
1
102
0
9
Order By: Relevance
“…[17,18] In addition, a few ABPs that enable non-reversible mechanism-based labeling of retaining β-galactosidases have been reported. These include suicide substrates bearing a latent quinone methide precursor as the aglycon to which a fluorescent or fluorogenic tag is attached [19][20][21][22] and 2-fluorogalactoside inhibitors in which the hydroxyl group at C6 is substituted with an azide, which enables two-step labeling via Staudinger-Bertozzi ligation. [23] To date, none of these probes has been used for the labeling of human retaining β-galactosidases.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] In addition, a few ABPs that enable non-reversible mechanism-based labeling of retaining β-galactosidases have been reported. These include suicide substrates bearing a latent quinone methide precursor as the aglycon to which a fluorescent or fluorogenic tag is attached [19][20][21][22] and 2-fluorogalactoside inhibitors in which the hydroxyl group at C6 is substituted with an azide, which enables two-step labeling via Staudinger-Bertozzi ligation. [23] To date, none of these probes has been used for the labeling of human retaining β-galactosidases.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies describing these approaches include (Keinan, 2005, and refs therein). The employment of the approaches have demonstrated that the substrate specificity (and/or the specific activity) of some artificial Abzs is comparable to or even higher than that of enzymes with the same catalytic activity (Barbas et al, 1997;Janda et al, 1997;Keinan, 2005, and refs therein).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic basis for the activity of such Abzs is becoming well understood (Janda et al, 1997;Thayer et al, 1999;Keinan, 2005, and refs therein). The field of artificial Abzs has been amply reviewed recently (Martin & Schultz, 1999;Suzuki, 1994;Keinan, 2005, and refs therein), for more detailed description of the relevant reactions.…”
Section: Introductionmentioning
confidence: 99%
“…124 I-TrapG can be converted by bG to form the quinine methide derivative of 124 I-Trap to quickly react with any nearby nucleophile moiety such as membrane proteins (23) (Fig. 1B).…”
mentioning
confidence: 99%